The Existential Burden of Quality Assurance: Academic Stress and Resilience Among Lecturers in an Indonesian Islamic University - Diana, Eka; Holifah, Holifah; Baharun, Hasan; Zamroni, Zamroni (SYAMIL: Journal of Islamic Education, 2026)
The quality assurance requirement of academic qualification to lecturers is gaining more and more eminent dynamics in the dynamics of higher education in Indonesia. The research will focus on the definition of pressure on the qualification of education and how the same can affect the mental health of lecturers and what the schools can do to balance the quality and their mental health. A qualitative approach was used to collect data in which a case study method was utilized. In-depth interviews, observation and documentation were used to gather the data. The findings of the research reveal that the stress of persisting to be productive in the writing industry, publication of scientific articles and higher level studies is likely to cause an endless cycle of academic anxiety. The institutional and social expectations are usually too much to bear and can lead to emotional burnout, loss of self-confidence and lack of motivation to work. This pressure appears not only as an administrative burden but also as an existential burden that threatens lecturers' mental balance and professionalism. Nevertheless, universities have taken strategic steps by strengthening the role of internal institutional units that control academic quality, as well as full support from university leaders through affirmative policies and tuition assistance. Another solution developed is an academic mentoring program and training to help lecturers upgrade their skills and increase their psychological resilience. This research confirms that higher education quality assurance relies not only on academic achievement but also on the balanced mental health of lecturers.